Reading George Grant in the 21st Century
XI, 299 p. 1 illus.
Keywords: “It is hard to believe that George Grant died over thirty years ago. He was the foremost combination of personality and intellect of his age. A commanding presence, he led many Canadians, and others, to a deeper understanding of their country and the world. This fine collection of original essays reminds us that we need his philosophical guidance as strongly now as we did when he published Lament for a Nation sixty years ago.” - William Christian, biographer and friend. Author, George Grant: A Biography, Editor Selected Letters, Time as History, Philosophy in the Mass Age, The George Grant Reader (with Sheila Grant). “George Grant was one of the most important and insightful Canadian thinkers of the 20th century. However, his ideas about nationalism, technology and the role of the university are more important now than ever. This volume of essays reinvigorates Grant as a contemporary thinker both of and ahead of his time.” - David Edward Tabachnick, Nipissing University. Author of The Great Reversal: How We Let Technology Take Control of the Planet George Grant (1918-1988) was one of Canada’s foremost public philosophers. Though his thought arose out of reflection on the history of political philosophy, pressing political concerns were never far from view. He was particularly adept at locating the causes of political developments in philosophical movements that were centuries in the making. This book reassesses his ideas in light of philosophical and political developments of recent decades, including the resurgence of nationalism, criticisms of globalization and technocracy, and the ideological realignments having a particularly noticeable effect on right-wing politics. The contemporary reader of Grant is thus able to reflect on his broader criticisms of modernity from within a slightly different historical articulation of modernity. Though George Grant died in 1988, the philosophical themes in his work remain relevant into the 21st century. Tyler Chamberlain lectures in political science and philosophy at various institutions including Trinity Western University and Kwantlen Polytechnic University. His primary research interests are early modern political theory and Canadian political thought. He earned his Ph.D in Political Science from Carleton University in 2018.